2022
DOI: 10.1007/s11046-022-00692-z
|View full text |Cite
|
Sign up to set email alerts
|

Lipid-Like Biofilm from a Clinical Brain Isolate of Aspergillus terreus: Quantification, Structural Characterization and Stages of the Formation Cycle

Abstract: Invasive infections caused by lamentous fungi have increased considerably due to the alteration of the host's immune response. Recently, Aspergillus terreus is considered an emerging pathogen and has shown resistance to amphotericin B treatment, resulting in high mortality. The development of fungal bio lm is a virulence factor, and it has been described in some cases of invasive aspergillosis. In addition, although the general composition of fungal bio lms is known, ndings related to bio lms of a lipid nature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 58 publications
1
1
0
Order By: Relevance
“…Our findings unequivocally reveal that exposure to UV radiation significantly induced the production of an extracellular matrix (ECM) compared to the control group. In particular, for A. alternata and A. niger, we observed the formation of ECMs and film-like ECMs with deeply embedded hyphae, consistent with the descriptions in Rayon-Lopez's research [65]. Additionally, Rayon-Lopez describes the occurrence of vesicular ECMs in A. terreus, a phenomenon which we observed in the F. culmorum and F. graminearum fungi post-UV radiation, accompanied by abundant mycelia embedded into the ECM.…”
Section: Impact Of Uv Radiation On the Metabolic Activity Of Microsco...supporting
confidence: 90%
“…Our findings unequivocally reveal that exposure to UV radiation significantly induced the production of an extracellular matrix (ECM) compared to the control group. In particular, for A. alternata and A. niger, we observed the formation of ECMs and film-like ECMs with deeply embedded hyphae, consistent with the descriptions in Rayon-Lopez's research [65]. Additionally, Rayon-Lopez describes the occurrence of vesicular ECMs in A. terreus, a phenomenon which we observed in the F. culmorum and F. graminearum fungi post-UV radiation, accompanied by abundant mycelia embedded into the ECM.…”
Section: Impact Of Uv Radiation On the Metabolic Activity Of Microsco...supporting
confidence: 90%
“…Another study on A. terreus conducted by Rayón-López et al on-biofilm formation showed the presence of nucleic acid, carbohydrates, proteins, and different lipid components. It has been observed that the lipid-like biofilm may be associated with increased AmB resistance in some A. terreus isolates ( Rayon-Lopez et al., 2023 ). Similarly, Sonia et al demonstrated biofilm formation in Amb-resistant isolate of A. terreus , suggesting secretory proteins play important role in induction or establishment of biofilms in A. terreus ( Shishodia et al., 2020b ).…”
Section: Drug Resistance and Biofilm Formation In Aspergill...mentioning
confidence: 99%